2020
DOI: 10.1002/ejhf.1988
|View full text |Cite
|
Sign up to set email alerts
|

A combined bioinformatics, experimental and clinical approach to identify novel cardiac‐specific heart failure biomarkers: is Dickkopf‐3 (DKK3) a possible candidate?

Abstract: Aims Cardiac specificity provides an advantage in correlating heart failure (HF) biomarker plasma levels with indices of cardiac function and remodelling, as shown for natriuretic peptides. Using bioinformatics, we explored the cardiac specificity of secreted proteins and investigated in more detail the relationship of Dickkopf‐3 (DKK3) gene expression and DKK3 plasma concentrations with cardiac function and remodelling in (pre)clinical studies. Methods and results The cardiac specificity of secreted proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Specifically, the accumulation of ROS and oxygen radicals occurs during the pathological progression of myocardial ischemia, reperfusion and cardiac remodeling, thereby damaging the tissues and causing cell necrosis and apoptosis ( 25 ). Piek et al ( 15 ) reported that NPPB may be a specific biomarker of HF and Shi et al ( 16 ) used NPPB as a biomarker of HF and proved that the sodium-glucose cotransporter 2 inhibitor empagliflozin may be effective for HF. The present study generated in vitro HF models by H 2 O 2 induction in AC-16 and HCM cells to mimic oxidative stress damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the accumulation of ROS and oxygen radicals occurs during the pathological progression of myocardial ischemia, reperfusion and cardiac remodeling, thereby damaging the tissues and causing cell necrosis and apoptosis ( 25 ). Piek et al ( 15 ) reported that NPPB may be a specific biomarker of HF and Shi et al ( 16 ) used NPPB as a biomarker of HF and proved that the sodium-glucose cotransporter 2 inhibitor empagliflozin may be effective for HF. The present study generated in vitro HF models by H 2 O 2 induction in AC-16 and HCM cells to mimic oxidative stress damage.…”
Section: Discussionmentioning
confidence: 99%
“…The present study generated in vitro HF models by H 2 O 2 induction in AC-16 and HCM cells to mimic oxidative stress damage. The increase in NPPB transcription and MFI of ROS was considered as success of the generated model ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, elevated NT-proBNP and BNP levels in patients with structural heart disease are associated with the risk of ventricular tachyarrhythmias and are predictive for sudden cardiac death and ventricular arrhythmias [ 61 , 62 ]. A recent bioinformatics study revealed that BMP-10 appears to be the only actively secreted protein that shows a similar cardiac restrictive expression to that of NPs [ 63 ]. This protein clearly deserves attention, but except for a study showing that circulating BMP10 can identify patients at risk of recurrent atrial fibrillation after ablation [ 64 ], the biomarker potential of this protein has not been explored.…”
Section: Cardiac-specific Plasma Protein Biomarkersmentioning
confidence: 99%
“…Moreover, preoperative DKK3 urine levels in patients undergoing cardiac surgery were predictive for post-operative acute kidney injury (AKI) and increased risk for long-term loss of kidney function 15 . Finally, in a large cohort of heart failure (HF) patients, plasma DKK3 levels were associated with several cardiovascular risk factors, including kidney function, atrial fibrillation, body mass index (BMI) and blood pressure 16 .…”
Section: Introductionmentioning
confidence: 99%